Interactive effects of dietary protein and fiber levels on total tract and apparent ileal nutrient digestibility, microbiota profiling, and fermentation products in pigs fed a blend of branched-chain volatile fatty acids - Benavides-Infante, Angie P.; Fresno-Rueda, Anlly M.; Rodrigues, Lucas Alves; Socha, Michael T.; Fernandes, Tatiane; St-Pierre, Benoit; Perez-Palencia, Jorge Y.; Levesque, Crystal L. (Frontiers in Veterinary Science, 2026)
IntroductionThe experiment investigated the interactions between diet protein and fiber and branched-chain volatile fatty acids (BCVFA) on nutrient digestion, fermentation products, and microbiome modulation in pigs.MethodsFourteen cannulated pigs (body weight 20.4 ± 1.4 kg) were used in a replicated 6 × 5 Youden square design with 6 diets and 5 periods for at least 11 observations per dietary treatment. Experimental diets were 2 × 2 + 2 arrangement, consisting of 4 BCVFA-diets (isobutyrate, isovalerate, and 2-methyl butyrate, 1:1:1) supplemented at 1%, with varying protein [low (LP; 15%) or normal (NP; 19%) protein] and fiber [low (LF: 11%) neutral detergent fiber (NDF) or high (HF: 17% NDF)]. The ‘+2’ diets were a positive LP-LF (PC) and a negative NP-HF (NC) control without BCVFA. Diets, fecal, and ileal digesta samples were analyzed for nutrients, fiber composition, AA, and titanium. Fecal samples were analyzed for bacterial composition.ResultsPigs fed BCVFA-supplemented NP-HF diets had the greatest AID for acid detergent fiber (ADF), acid detergent lignin, cellulose, and hemicellulose, and the greatest ATTD for ADF (p < 0.05). The AID of AA was greater (p < 0.05) in pigs fed LP-LF PC diet compared to LP-LF BCVFA-supplemented diet (p < 0.05). There were no interactions (p > 0.05) between fiber and protein levels for volatile fatty acids (VFA) concentration in ileal and fecal samples. Feeding high fiber diets supplemented with BCVFA resulted in greater (p < 0.05) concentration of acetic, propionic, butyric, and total VFA production in fecal samples. Fecal bacteria affiliated to Erysipelotrichaceae were found in higher abundance in the BCVFA-supplemented NP-HF diet compared to its non-supplemented control (p < 0.05). Similarly, candidate bacterial strains of Turicibacter sanguinis (OTU Ssd-110) and Romboutsia timonensi (OTU Ssd-23) were more highly represented in the fecal microbial communities of pigs fed the BCVFA-supplemented NP-HF diet compared to its non-supplemented control (p < 0.05).ConclusionSupplementation of 1% BCVFA in swine diets containing higher fiber and typical crude protein can optimize digestive efficiency, particularly at the ileal level, which was associated with improvements in nutrient digestibility potentially mediated by microbiome modulation. This may represent an opportunity to feed simpler diets, improving the efficiency and sustainability of swine production.